Neuropsychological Tests for Multiple Sclerosis: Validation of a battery for the Portuguese Population - Neves, M.; Sousa, C.; Passos, A. M.; Ferreira, A.I.; Sá, M. J. (ECPA 14, 2017)
Introduction: The Brief Repeatable Battery of Neuropsychological Tests (BRBN-T) has proved to be one of the most sensitive measures for detecting cognitive impairment in Multiple Sclerosis (MS). The goal of this study was to adapt and validate this battery to the Portuguese population of MS patients. Methods: The study was organized in four main tasks: We started by translating and adapting the battery into Portuguese language, regarding the international guidelines for the effect (Task 1) and we tested the experimental version on a sample of 50 healthy subjects to select final items (Task 2). The Portuguese version of BRBN-T (Task 3) was applied to a stratified control national sample of 334 individuals (stratification criteria: age, sex, educational level and geographic location) and to a clinical sample of 127 MS patients from eight national hospitals. Through the exploration of its psychometrics properties, we produced the Portuguese norms of BRBN-T (Task 4). Results: The normative data is presented as a regression-based formula to adjust test scores for gender, education and age, and the results reveal the ability that BRBN-T has to differentiate between MS patients and healthy participant’s performance. Conclusion: This study clearly contributed to improve the actual context of neuropsychological assessment in Portugal, by providing a new set of instruments which can be used in the clinical practice and in future studies, even in areas beyond Psychology and Medicine. Moreover, clinical trials and longitudinal studies will benefit from rigorous, precise and discriminative support concerning neuropsychological assessment.